La investigación en administración - Varón Rojas, Diego Hernán; Rincón Aguirre, Lina Marcela; Perafan Galvis, Ana Jimena; Maldonado Vásquez, Maritza Adriana; Londoño Cardozo, José; Loboa Ortega, Edwar Eli; Benavides-Sánchez, Edward Andrés; Castro Ruíz, Camilo Andrés; Brand Narváez, Miguel Ángel; Galvis Galvis, Ana Cristina; Salazar Valencia, Paola Andrea; Quintero Sepúlveda, Isabel Cristina; et al. (Universidad Santiago de Cali, 2025)
Published